Local Projections vs. VARs - Li, Dake,Plagborg-Møller, Mikkel,Wolf, Christian (National Bureau of Economic Research, 2022)
We conduct a simulation study of Local Projection (LP) and Vector Autoregression (VAR) estimators of structural impulse responses across thousands of data generating processes, designed to mimic the properties of the universe of U.S. macroeconomic data. Our analysis considers various identification schemes and several variants of LP and VAR estimators. A clear bias-variance trade-off emerges: LP estimators have lower bias than VAR estimators but substantially higher variance at intermediate and long horizons. Consequently, unless researchers are overwhelmingly concerned with bias, shrinkage via Bayesian VARs or penalized LPs is attractive
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Zeitreihenanalyse; IV-Schätzung; VAR-Modell; Big Data; Data Analytics; Schätztheorie; Local Projection Method; Data Generation Process; Time-Series Models; Dynamic Quantile Regressions; Dynamic Treatment Effect Models; Diffusion Processes; State Space Models; Instrumental Variables (IV) Estimation